Sistem Rute Terpendek Pencarian Buku Di Perpustakaan Menggunakan Algoritme Dijkstra - Muh. Syifau Mubarok; Dahnial Syauqy; Hurriyatul Fitriyah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The library is considered as a convenient place to read, because the library provides a collection of books and other publications services that are provided to the general public or certain groups. Lots of information can be obtained from the library includes scientific, recreational, religious and entertainment that are human needs. However, according to a survey conducted by UNESCO in 2015 stated that the reading interest of Indonesian society is very low. The lack of interest in reading the community can be affected by several factors such as, the minimal number of libraries and the lack of decent facilities in the library. For example, the more extensive a library, the more variations of book categories and certainly directly proportional to the large number of shelves arranged. Doing a random search manually is the way that most often done, so it will wasting time, especially if the library visitors are visiting the library for the first time and don't know the location of the shelves and the arrangement of the book placement. With the research located on the white label room of the central library of Brawijaya University, the writer made an Arduino-based system which was planted in a book basket, which in the system contained a list of book categories in the library as well as the shelf location where the books were stored. The visitors only need to select the category of books that they want to borrow then the system will process it. The resulting output is the shortest bookshelf route through the LCD on the system by first mapping the existing bookshelves in the library by calculating the shortest distance of the book sought on the nearest shelves from the starting point. With the research located on the white label room of the central library of Universitas Brawijaya, the results from 10 random route search samples the system succeeded in determining the right route with an accuracy value of 100%. It is proven that the system works well besides of that the kind system is an embedded system that is installed in a book basket, so it will make it easier for the visitors if they want to borrow a lot of books in large quantities. On another test was done by testing the execution time required by the system to find the shortest route, the results of 10 tests using random samples only require a very short time with an average of 4.2 milliseconds.